Organizational culture: An overview and bibliometric analysis (Asian Journal of Economics and Business Management, 2023)
Culture is believed to be the most important factor in maintaining an organization's competitive advantage and determining the success or failure of an organization in achieving its goals. This research was conducted to fill the gaps in previous organizational culture research by using more recent research data. Describing the discussion related to an organizational culture that has been published in 2017-2023 is the purpose of this study. This research is a type of bibliometric literature study using the help of VOSviewer software to analyze data. The data sources used as references in this study were obtained from the Science Direct and Mendeley databases for 2017 - 2023. Thirty-four articles were used as material for analysis in this study. This study discusses 10 articles with the highest number of citations. This study's results indicate that seven groups of writers have research links in the field of organizational culture. Employee performance, organizational change, conflict management, safety culture, organizational innovation, and leadership style are research variables often related to organizational culture. The topic of organizational culture research is still widely used in recent years.